2022
DOI: 10.1212/wnl.0000000000200386
|View full text |Cite
|
Sign up to set email alerts
|

SEEG Functional Connectivity Measures to Identify Epileptogenic Zones

Abstract: Background and Objective:Functional connectivity (FC) measures can be used to differentiate epileptogenic zones (EZs) from non-EZs in patients with medically refractory epilepsy. However, little work has been done to evaluate stability of stereoelectroencephalography (SEEG) FC measures over time and their relationship with anti-seizure medication (ASM) use – a critical confounder in epilepsy FC studies to date. In this study, we aim to answer the following questions: 1) are SEEG FC measures stable over time, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…However, Kramer and colleagues demonstrated the emergence of stable network pattern across long-term recordings . Similarly, others studies have reported stability of the functional connectivity results across days of intracranial EEG recordings in patients with epilepsy Jiang et al, 2022;Mormann et al, 2000;Paulo et al, 2022;Schevon et al, 2007). This result strengthens the confidence in the use of connectivity data for EZ delineation purpose in practice.…”
Section: Association With Other Variablessupporting
confidence: 74%
See 4 more Smart Citations
“…However, Kramer and colleagues demonstrated the emergence of stable network pattern across long-term recordings . Similarly, others studies have reported stability of the functional connectivity results across days of intracranial EEG recordings in patients with epilepsy Jiang et al, 2022;Mormann et al, 2000;Paulo et al, 2022;Schevon et al, 2007). This result strengthens the confidence in the use of connectivity data for EZ delineation purpose in practice.…”
Section: Association With Other Variablessupporting
confidence: 74%
“…Notably, the model performed equally well in the subset of patients who were seizure-free after surgery (higher confidence in the exact definition of the epileptogenic zone). Recently, Paulo and colleagues investigated the impact of time in EMU, changes in antiseizures medications doses, seizure burden, and differences between eyes-closed formal resting-state, and eyes-open pseudoresting states on interictal SEEG FC (imaginary coherence and partial directed coherence computed in the alpha band) (Paulo et al, 2022). They confirmed that non-directed and inward connectivity measures are higher in EZ compared to NIZ, but most importantly demonstrated that: 1) FC measures are stable over time; 2) FC measures are not influenced by the seizure burden; 3) antiseizure medication dose may influenced some FC measures (imaginary coherence with smaller difference between EZ and NIZ in case of smaller dose of antiseizure medication) but not some other (partial directed coherence); 4) the type of resting-state (formal eyes-closed or not) may influence some FC measures (partial directed coherence with higher difference between EZ and NIZ during formal eyes closed resting state) but not some other (imaginary coherence).…”
Section: Seeg Studiesmentioning
confidence: 99%
See 3 more Smart Citations